Determination Rule for α, β Directions and φ in Teaching of Slip-Line Theory. (2nd February 2023) - Mei, Ruibin; Bao, Li; Gao, Han; Zhang, Xin
Abstract : In the teaching of plastic mechanics and applications of slip-line theory using conventional methods, multivalued results are usually caused by the uncertain direction of the slip line and dip angles. Determination rules for the α and β directions and φ values are proposed to improve slip-line theory according to the particle flow law under the effect of principal stress, and slip lines and dip angles suitable for a typical stress boundary problem are described. The α and β slip lines should simultaneously point to or away from the intersection, and the synthetic direction of the slip lines should point to the first principal stress σ 1 or away from the direction of the third principal stress σ 3 . When the Hencky stress equation of the α line is applied, two points on the α line should maintain the same direction, and the absolute value of the φ difference should be less than or equal to π . Moreover, the α line of two points should simultaneously point to the inner and outer normal direction of the β line when the Hencky stress equation of the β line is used. The average stress and critical load of plastic deformation in the plane lath V-notch tension are solved using slip-line theory. Both the calculated critical stress and the load maintain uniformity using different slip lines and dip angles, and the proposed determination rule reliably avoids multivalued solutions. This is important for students and researchers in correctly understanding and applying slip-line theory.